Construction of a prayer room to improve the smooth running of worship and social activities in Lebak village: Pembangunan musholla untuk meningkatkan kelancaran kegiatan ibadah dan sosial di desa Lebak - Heri Sugiantoro; Sholchan Ghozali (Jurnal Pengabdian Masyarakat (Bisma), 2025)
A prayer room is a worship facility that not only functions as a place for worship activities, but also functions as a center for social activities in community associations. This activity involved several local communities in Blooto village where planning, evaluation and implementation were previously held. This activity was carried out on 15 December 2023 - 21 April 2024 starting from laying the first stone until the inauguration of the building. The method used is Participatory Action Research (PAR), where the community is directly involved in the process of laying the first stone until the inauguration. The results show an increase in the quality of facilities, religious and social activities, as well as close relationships with the community in mutual cooperation. This experience proves the important role of the prayer room as a facility and the community the importance of mutual cooperation, thereby creating conditions of harmony and faith.